Global Investment Promotion Best Practices 2012 : Seizing the Potential for Better Investment Facilitation in the MENA Region - International Finance Corporation; World Bank; Multilateral Investment Guarantee Agency (World Bank Group, Washington, DC, 2014)
The drop in foreign direct investment (FDI) flows to the Middle East and North Africa (MENA) region over the past three to four years stems in part from the aftermath of the recent global economic crisis, and in part from the uncertainties created by the political and social changes in the region that have characterized the so-called Arab Spring. However, the medium-term outlook may be more positive as greater governmental transparency and less cumbersome business environments are expected to foster FDI, stimulate entrepreneurship, and create jobs. The Global Investment Promotion Best Practices (GIPB) 2012 report presents well-timed and useful insights into the capacities of IPIs to perform their investment facilitation function. Thus a careful analysis of GIPB findings can be important in helping MENA Investment Promotion Intermediary's (IPIs) introduce targeted improvements that will enable them to increase FDI flows into the region. The GIPB 2012 assessment also detected a number of procedural hitches, such as difficulty in contacting an IPI or a relevant project manager in spite of repeated attempts, failure to provide acknowledgment of inquiry receipt, and problems locating investor e-mails. Following the recent upheavals experienced in the region, MENA IPIs should take full advantage of the outstanding opportunities offered by online and offline communication tools to mitigate investors' risk perceptions and influence their decisions through the provision of accurate and up-to-date information on the investment location. For the purpose of this report, the analysis of GIPB data has been complemented with qualitative and quantitative information collected through a survey of MENA IPI institutional and operational characteristics, including a number of in-depth telephone interviews with selected IPIs across the region.